PBL and society: University-industry collaborative learning - Sandoval-Carvajal, Maria-Marta (2018)
International Symposium on Project Approaches in Engineering Education Volume 8 (2018). Proceedings of the PAEE/ALE’2018, 10th International Symposium on Project Approaches in Engineering Education (PAEE) and 15th Active Learning in Engineering Education Workshop (ALE) University of Brasília, Brasília, Brazil - 28 February - 02 March 2018.